LATE PALAEOCENE-EARLY EOCENE DINOFLAGELLATE CYSTS FROM THE TURGAY STRAIT, KAZAKHSTAN; CORRELATIONS ACROSS ANCIENT SEAWAYS - Iakovleva A.I.; Cavagnetto C.; Brinkhuis H. (My University, 2001)
The results of a quantitative palynological analysis, emphasizing organic-walled dinoflagellate cysts (dinocysts), of Palaeocene–Eocene deposits exposed in the Sokolovsky Quarry (Turgay Trough, Northern Kazakhstan) are presented here. Located in the ancient Turgay Strait, a former seaway presumed to have connected the Tethyan and Boreal oceans and seas in the early Palaeogene, the Sokolovsky Quarry outcrop occupies a key position for the analysis of connections between these realms.In general, the dinocyst succession of Sokolovsky closely resembles coeval Arctic Ocean–North Sea Basin counterparts; only in one interval endemic and/or possibly Tethyan species co-occur. The successive dinocyst assemblages allow recognition of the Late Palaeocene–Early Eocene P5a, P5b, P6a, P6b and E2 zones established in the North Sea Basin. The succession is interpreted to represent parts of several third-order sea level cycles correlative with those recognised in the North Sea Basin. Detailed comparison with similar studies from southeastern England allows the recognition of (parts of) third order cycles Thanetian-1 (Tht-1), 2, 4, 5, and Ypresian (Ypr)-3. In addition, two important stratigraphic gaps within the Palaeocene–Eocene succession are recognised, possibly reflecting times of sea level lowering. These gaps are inferred from (1) the absence of a complete P5b/P6a transition, (2) the absence of zone E1, and (3) (bio)sequence stratigraphy.Combined results indicate that the Turgay Strait flooded from the north between ∼57.8 and 57.1 Ma (cycles Tht-1 and 2, in part, with a minor missing section). During the ‘second’ phase of Turgay-flooding (∼56.4–55.3 Ma), evidence may be taken to indicate increased influence from the Tethyan Ocean and/or warmer conditions. Deposits reflecting the Late Palaeocene Thermal Maximum, associated with this interval, are present at Sokolovsky Quarry. This interval is marked by abundant Apectodinium spp., including A. augustum, and organic-rich layers. A third flooding is correlative to the London Clay transgression (from ∼54.5 Ma).From our study, no decisive evidence has become available that confirms that a connection between the Arctic and Tethyan oceans via the Turgay Strait in the early Palaeogene existed. Nevertheless, during intervals of major sea level fall, the Turgay Strait depression may be regarded to have been an important feature for migrating terrestrial biota.Four new wetzeliellioid taxa Apectodinium sp. A, Apectodinium sp. B, Wilsonidium? sp. A and Wilsonidium? sp. B are described from the Palaeocene part of the section.
Keywords: Palaeocene; Eocene; dinocysts; Turgay Trough; Kazakhstan; Cenozoic::Paleogene::Eocene; Кайнозой::Палеоген::Эоцен